Synergistic effect of doping with nitrogen and molybdenum on the photocatalytic properties of thin titania films. (April 2015) - Ratova, M.; West, G.T.; Kelly, P.J.; Xia, X.; Gao, Y.
Abstract: Doping of titania with metal and non-metal elements provides a simple and efficient pathway to significant enhancement of photocatalytic properties. In this work titania thin films co-doped with molybdenum and nitrogen were prepared by reactive magnetron sputtering. Additionally, coatings doped only with nitrogen were prepared under identical deposition conditions for comparison purposes. Coatings were annealed at 873 K in air and analysed by Raman spectroscopy, XRD and XPS. Photocatalytic properties of the coatings were evaluated on the basis of the photodegradation rate of methylene blue dye under UV, fluorescent and visible light. It was found that the photocatalytic activity of co-doped samples was significantly higher than that of N-doped coatings. Unlike N-doped titania films, co-doped coatings exhibited high photocatalytic activity under the fluorescent light source and noticeable activity under visible light. The possible mechanism for the enhancement of the photocatalytic activity of Mo–N co-doped titania coatings is discussed. Highlights: Titania coatings co-doped with Mo and N were compared with single doped coatings. The co-doped coatings showed significantly higher photocatalytic activity. The co-doped coatings also showed visible light activity.